Potential of Biochar Filters for Onsite Wastewater Treatment: Effects of Biochar Type, Physical Properties and Operating Conditions - Luis Fernando Perez-Mercado (Water, 2018)
The potential of biochar as a filter medium for onsite wastewater treatment was investigated in five sub-studies. Sub-study 1 compared pollutant removal from wastewater using pine-spruce biochar, willow biochar and activated biochar (undefined biomass) filters. Sub-study 2 investigated the effects of particle size (0.7, 1.4 and 2.8 mm) on pollutant removal using pine-spruce biochar filters. In sub-studies 3 and 4, the effects of the hydraulic loading rate (HLR; 32⁻200 L m−2) and organic loading rates (OLR; 5⁻20 g biochemical oxygen demand (BOD5) m−2) on pollutant removal using pine-spruce biochar filters were investigated, while sub-study 5 compared pollutant removal in pine-spruce biochar filters and in sand. The removal of chemical oxygen demand (COD), total nitrogen (Tot-N), ammonium nitrogen (NH4-N), phosphates (PO4-P) and total phosphorus (Tot-P) was monitored in all sub-studies. All types of biochar and all particle sizes of pine-spruce biochar achieved a high degree of removal of organic material (COD > 90%). Removal of Tot-P and PO4-P was higher in willow biochar and activated biochar (>70%) than in pine-spruce biochar during the first two months, but then decreased to similar levels as in pine-spruce biochar. Among the particle sizes tested, 0.7 mm pine-spruce biochar showed the lowest amount of Tot-P removal, while 2.8 mm pine-spruce biochar showed the lowest level of NH4-N removal. Different OLRs and HLRs did not influence COD removal (94⁻95%). Pine-spruce biochar showed a better degree of removal of Tot-N than sand. In conclusion, biochar is a promising filter medium for onsite wastewater treatment as a replacement or complement to sand, achieving high and robust performance regardless of the parent material, particle size or loading conditions.